Retrievable inferior vena cava filters: factors that affect retrieval success - Geisbüsch, Philipp (CardioVascular and interventional radiology, 2012)
PurposeTo report and analyze the indications, procedural success, and complications of retrievable inferior vena cava filters (rIVCF) placement and to identify parameters that influence retrieval attempt and failure.MethodsBetween January 2005 and December 2010, a total of 200 patients (80 men, median age 67 years, range 11-95 years) received a rIVCF with the clinical possibility that it could be removed. All patients with rIVCF were prospectively entered into a database and followed until retrieval or a decision not to retrieve the filter was made. A retrospective analysis of this database was performed.ResultsSixty-one percent of patients had an accepted indication for filter placement; 39% of patients had a relative indication. There was a tendency toward a higher retrieval rate in patients with relative indications (40% vs. 55%, P = 0.076). Filter placement was technically successful in all patients, with no procedure-related mortality. The retrieval rate was 53%. Patient age of >80 years (odds ratio [OR] 0.056, P > 0.0001) and presence of malignancy (OR 0.303, P = 0.003) was associated with a significantly reduced probability for attempted retrieval. Retrieval failure occurred in 7% (6 of 91) of all retrieval attempts. A time interval of > 90 days between implantation and attempted retrieval was associated with retrieval failure (OR 19.8, P = 0.009).ConclusionsPatient age >80 years and a history of malignancy are predictors of a reduced probability for retrieval attempt. The rate of retrieval failure is low and seems to be associated with a time interval of >90 days between filter placement and retrieval.